Stack overflow data explorer : dictionary tool for software engineering terms from user-generated content - Wang, Ximing (2016)
In this information age, many informal texts were generated and put up online, these user-generated-content may contain a lot of misspelled terms and abbreviations which affect people’s understanding. These cases happen often in the software engineering community website or the technology blog. The various forms of the same term can be misleading. Whenever people encounter a software engineering term that they may not understand, additional searches need to be done to get the explanation. Not mentioning the query like the what library to use for a certain task, many readings, information extraction and comparison needed to be done. This project aims to shorten the time taken for look up these software engineering terms online and assist people to find the direct answer to their query.